Leadership mindset [ innovation and learning in the transformation of schools - Kaser, Linda; Halbert, Judy , 1949- (London ;New York : Routledge, 2009)
Why are some leaders able to raise student achievement in schools in the most challenging circumstances whilst other leaders struggle to simply maintain the status quo? This title argues that there
1. Moving from Sorting to Learning - New Mindsets Required -- 2. Intense Moral Purpose -- 3. Trust - Relationships First -- 4. Inquiry - Questions before Directions -- 5. Learning for Deeper Understanding -- 6. Evidence-Seeking in Action -- 7. Learning-Oriented Design -- 8. Leadership, connections and good work
Description based on print version record
Includes bibliographical references (p 151-160) and index
Keywords: Educational innovations; Educational leadership; School management and organization